1979
DOI: 10.1038/sc.1978.66
|View full text |Cite
|
Sign up to set email alerts
|

An exercise test to evaluate fitness for wheelchair activity

Abstract: Abstract. The purpose of this study was to develop a wheelchair ergometer (WERG) test to evaluate fitness for manual wheelchair activity.Thirty able-bodied females participated in a progressive intensity, discontinuous test where exercise bouts were 4 min in duration interspersed with 5-min rest periods. Physiological responses of oxygen uptake (V02), respiratory exchange ratio (R), net mechanical efficiency (ME), pulmonary ventilation (VO) and heart rate (HR) were determined during the final minute of exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

1982
1982
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 9 publications
0
19
0
3
Order By: Relevance
“…Other diagnoses included spina bifida (4%), cerebral palsy (2%), traumatic injury (3%), amputees (1%), polio (1%), and bilateral tarsal tunnel syndrome (1%). Table 1 lists eight interval training studies, [21][22][23][24][25][26][27][28] of which three included a control group, [26][27][28] though none were randomised controlled trials. Four studies included participants with spinal-cord injury, 21,22,24,25 and three included healthy ambulatory participants.…”
Section: Resultsmentioning
confidence: 99%
“…Other diagnoses included spina bifida (4%), cerebral palsy (2%), traumatic injury (3%), amputees (1%), polio (1%), and bilateral tarsal tunnel syndrome (1%). Table 1 lists eight interval training studies, [21][22][23][24][25][26][27][28] of which three included a control group, [26][27][28] though none were randomised controlled trials. Four studies included participants with spinal-cord injury, 21,22,24,25 and three included healthy ambulatory participants.…”
Section: Resultsmentioning
confidence: 99%
“…1 The correct determination of VO 2max requires a maximum degree of exertion. An incremental exercise test for wheelchair athletes can be performed on an ergometer with armcranking, 10,11 on a treadmill with increasing velocity, 12 with increasing resistance 4,13 or increasing inclination and increasing velocity. 14 Our athletes reached a VO 2max of 35.1+4.9 ml/min/ kg (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that an appropriately designed lower limb endurance exercise training program may significantly increase the V02 max of sedentary non-disabled individuals, as well as their stroke volume, cardiac output, 02 arteriovenous difference, and the oxidative capacity of muscle. Similarly, it has been shown that the exercise capacity of able bodied subjects may be increased by upper limb endurance training (12,40,41), although the response is smaller and less consistent than after leg exercise training. A number of studies on the effects of upper limb endurance exercise on individuals with SCI have shown significant increases (18-50%) in V02 max and other corresponding measured parameters (30,32,42), at least if the cord lesion was at T7 or below (44).…”
Section: Reduced Cardiovascular Fitnessmentioning
confidence: 94%